Ketone bodies production and utilization by the two breast cancer compartments/ An immunohistoche-mical study in Kurdistan region-Iraq - Yasseen, Hadeel Adnan; Sahib, Rawand Tajuldeen; Ezzaddin, Shahow Abdulrehman (Sulaimani Journal for Pure and Applied Sciences, 2018)
Background Because of the close relationship between the cancer cells and cancer associated fibroblasts, it is increasingly clear that the development of cancer cannot be dissociated from its local microenvironment. Many previous researches were done to prove the role of cancer associated fibroblasts in fueling the cancer epithelial cells with ATP and lactic acid. Objective This study was designed to clarify the role of cancer associated fibroblasts in feeding the breast cancer epithelial cells with ketone bodies and indirectly to anticipate the efficacy of ketogenic diet in breast cancer patients. Materials and methods Forty selected cases of invasive breast carcinoma not otherwise specified (NOS) with a mean age of 47.83 ± 12.04 were included in this study and immunohistochemically stained with two mitochondrial enzymes antibodies: HMGCS2 and ACAT1; that play important roles in synthesis of the primary ketone body; acetoacetate and in ketone breakdown (ketolysis) during the fat processing respectively. Result Our result showed that both cell compartments harbor the enzymes needed for ketone bodies production and utilization. Cancer epithelial cells contain HMGCS2 and ACAT1 in 97.5% and 87.5% respectively. While cancer associated fibroblasts contain HMGCS2 and ACAT1 in 95% and 67.5% respectively. Conclusion both compartments can efficiently produce and utilize the ketone bodies, so indirectly we can say that ketogenic diet may have limited role in breast cancer management
Keywords: cancer associated fibroblasts; ketone bodies; ketogenic diet; mitochondrial enzymes